HUMAN CAPITAL AS AN OBJECT OF SOCIAL MANAGEMENT IN ECONOMICS AND POLITICS - Barsukova, Tatiana I.; Paliy, Irina G.; Bahutashvili, Tatiana V.; Plotnikova, Tatiana V.; Spektor, Lyudmila A.; Maksimov, Vladimir Yu. (International Journal of Psychosocial Rehabilitation, 2020)
The global historical experience has shown that technologization of entire industries of manufacture, management and public administration can notedly lead to abolition of once quite popular professions. Therefore, the human capital that does not contribute to development of the country and system of its innovative economy branches will be defined as passive. The task of public administration bodies is to form active human capital, capable of advancing development in the long-term perspective of rather distant future, taking into account market environment and global development trends. The main goal of the study is to analyze state policy prospects of investing in human capital in conditions of stimulating national civil society model (in the context of Russia). The methodological background to the study of human capital as a key factor in economic and social development was formed by ideas of political economy classical scientists. The modern theory the human capital is treated as an autonomous source of income, depending on the skills, knowledge and abilities of a person, including physical and mental state. The study of specific aspects and general dynamics of state investment in human capital allows for the conclusion that Russian citizens generally have a fairly high level of human capital, mainly due to high level of education; the state in Russian socio-political and economic realities can be considered as the main investor in human capital of population. However, high risks associated with loss of human capital remain in the area of insufficient funding for medicine and support for educational initiatives. The results suggest that human capital participating in total economic growth must be: adaptive to real technological projects; liquid, capable of moving in different economic environments, generating high income; easily integrated into various investment projects; resistant to market challenges and the consequences of global crises. Scientific novelty of the study consists in totality of the obtained results, revealing the features of formation and implementation of human capital in the context of global challenges and threats